Pelatihan Pengembangan Perangkat Pembelajaran Berbasis Kurikulum Merdeka melalui Model PjBL pada Guru MGMP SMA se-Kota Tasikmalaya - Apiati, Vepi; Heryani, Yeni; Hermanto, Redi; Muzdalipah, Ipah (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
Activities for implementing the Community Service Program Featured Study Program Scheme (PbM-PUPS) by the Mathematics Education Department towards the High School Mathematics MGMP which is implemented in the form of "Workshop: Development of Independent Curriculum Based Learning Tools Through the PJBL Model for High School Mathematics MGMP Teachers throughout the City of Tasikmalaya", provide benefits and convenience for teachers in compiling teaching materials, Student Worksheets, and evaluation tools that will be used in learning, provide opportunities for mathematics teachers to gather, discuss, and share their experiences and knowledge in teaching mathematics and discuss changes or development of the independent curriculum, and discussing how to implement this curriculum well and effectively in mathematics learning in the classroom.